Trichilemmal Horn: A Case Report - Rodrigo C. Davanço; Domingos J. Neto; Carolina B. Milanez; António J. Tebcheran (Sociedade Portuguesa de Dermatologia e Venereologia, 2021)
Trichilemmal horn or trichilemmal keratosis is a benign neoplasm, that occurs more frequently in females and in the age group over 50 years old. Clinically, it presents as a cutaneous horn and histologically shows trichilemmal keratinization at the base of the lesion. As an uncommon pathology, in this case report, we will present the case of a young man (14 years old), presenting a keratotic lesion on the forehead for eight months, which revealed the diagnosis of trichilemmal horn after lesion exeresis and anatomopathological analysis.